The Influence of The Sustainable Food Garden Program (P2L) Implementation on The Empowerment of Women's Farmer Groups with Social Entrepreneurship as A Moderating Variable In Denpasar City - Ni Luh Gede Nirmala Devi; I Dewa Putu Oka Suardi; Ketut Budi Surusa (Publikasi Indonesia, 2025)
This study aims to examine the implementation of the P2L Program and the empowerment of women farmer groups in Denpasar City, and analyze with social entrepreneurship as a moderation variable to develop programs and strengthen the empowerment of women farmer groups so that more substantial benefits are felt and the program can be held sustainably. This study uses primary and secondary data sources, as well as quantitative and qualitative data types. This study was conducted on 80 respondents from four sub-districts in Denpasar City with proportionate random sampling technique and sample selection was carried out by accidental sampling technique. The analysis of the implementation of the P2L Program on the empowerment of farmer women groups, as well as its interaction with social entrepreneurship as a moderation variable was processed with the SmartPLS application version 4.1.0.1. Furthermore, the test results are interpreted by quantitative descriptive methods. Based on data from the research location, it is known that the implementation of the P2L Program in Denpasar City is quite good and the empowerment of women farmer groups is relatively high. The results of the analysis of the study show that, the implementation of the P2L Program in Denpasar City is quite good and the empowerment of P2L farmer women groups in Denpasar City is relatively high, social entrepreneurship moderates by strengthening the influence of the implementation of the P2L Program on the empowerment of farmer women groups in Denpasar City.